Laminated lithium ion battery adopting safe prime coat slurry to improve safety performance
By applying a safety coating on the surface of the positive current collector of the lithium-ion battery, the temperature sensitivity of lithium iron phosphate and PTC materials is used to solve the safety problems of lithium-ion batteries under extreme conditions, and the battery is achieved with high safety and low cost production.
Patent Information
- Application Number
- CN202510678769.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-05-26
- Publication Date
- 2025-08-26
AI Technical Summary
Traditional lithium-ion batteries are prone to short circuits and heat generation due to contact with positive and negative electrodes under extreme conditions, causing safety accidents, and the prior art is difficult to effectively improve their safety performance.
The surface of the positive electrode current collector is equipped with a safety coating. The coated safety primer is made of mixed lithium iron phosphate, PTC material, conductive agent and binder to form a temperature-sensitive safety coating, preventing the embeddedness and detachment of active lithium and reducing the electrochemical reaction rate.
It improves the safety performance of lithium-ion batteries in extreme cases, avoids safety accidents, reduces electrochemical reaction rates, enhances battery capacity and reduces capacity losses, and has high safety and low cost.
Smart Images

Figure CN120545514A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of lithium ion batteries, and in particular relates to a laminated lithium ion battery which adopts a safety primer slurry to improve safety performance. Background Art
[0002] As a new energy product, lithium-ion batteries have been widely used in a variety of fields, including drones, digital products, wearable security products, and power tools. However, when used under irregular conditions, such as overcharging, nail puncture, and short circuits, traditional lithium-ion batteries are prone to generating excessive heat, leading to separator shrinkage, positive and negative short circuits, and other safety accidents such as battery fires. The main reason for this is that the positive and negative electrodes, in extreme cases, directly contact or indirectly release each other, causing a short circuit, which generates a large amount of heat. Therefore, increasing the battery's ohmic internal resistance and reducing the short-circuit current are crucial to improving the safety performance of lithium-ion batteries.
[0003] In order to solve this problem, it is necessary to prime the surface of the aluminum foil to develop a set of high-safety lithium-ion batteries that can support lithium cobalt oxide or ternary system puncture at 4.4V and below. Summary of the Invention
[0004] The technical problem to be solved by the present invention is to address the shortcomings of the above-mentioned prior art and provide a laminated lithium-ion battery that uses a safety primer slurry to improve safety performance. By providing a safety coating on the outer surface of the positive electrode current collector, the laminated lithium-ion battery not only provides active lithium ions for lithium insertion and extraction, thereby increasing battery capacity, but also has a temperature-sensitive internal resistance. As the temperature rises to a critical point, the internal resistance increases instantaneously, effectively preventing the insertion and extraction of active lithium, reducing the electrochemical reaction rate, improving the battery's safety performance in extreme conditions, and preventing safety accidents.
[0005] In order to solve the above technical problems, the technical solution adopted by the present invention is: a laminated lithium-ion battery that uses a safety primer slurry to improve safety performance, characterized in that the laminated lithium-ion battery includes a battery shell and a battery cell in the battery shell, the battery cell includes a laminated positive electrode sheet, a separator and a negative electrode sheet and an electrolyte, the positive electrode sheet includes a positive electrode collector, the outer surface of the positive electrode collector is provided with a safety coating, the outer side of the safety coating is coated with a positive electrode slurry, the safety coating is formed by spraying the safety primer slurry onto the surface of the positive electrode collector and then drying it, the safety primer slurry is prepared by mixing lithium iron phosphate, PTC material, conductive agent and binder, using N-methylpyrrolidone as a dispersion medium, and high-speed stirring.
[0006] The present invention provides a safety coating on the outer surface of the positive electrode current collector, which not only provides active lithium ions for lithium insertion and extraction, thereby improving the battery capacity, but also the internal resistance of the safety coating is sensitive to temperature. As the temperature rises to a critical point, the internal resistance increases instantly, which can effectively prevent the insertion and extraction of active lithium, reduce the electrochemical reaction rate, improve the safety performance of the battery under extreme conditions, and avoid the occurrence of safety accidents.
[0007] The crystal structure and chemical properties of the lithium iron phosphate in the safety primer material of the present invention are stable and can improve the safety performance of the battery cell. At the same time, the addition of lithium iron phosphate to the safety primer material can increase active lithium and reduce the capacity loss of the battery cell. The PTC material has a PTC effect in a high temperature environment. When the temperature reaches a certain critical point, the internal resistance will increase instantaneously, which is beneficial to increase the internal resistance of the battery cell, increase the resistance to electron conduction, reduce the electrochemical reaction rate, improve the safety performance of the battery under extreme conditions, and avoid the occurrence of safety accidents. The conductive agent in the safety primer material mainly improves the conductive performance of the safety primer material, and the binder mainly bonds the conductive agent, lithium iron phosphate and PTC material into a whole through chemical bonds, etc., thereby reducing the contact impedance between the materials.
[0008] The aforementioned laminated lithium-ion battery employing a safety primer slurry to enhance safety performance is characterized in that the mass ratio of lithium iron phosphate, PTC material, conductive agent, and binder in the safety primer slurry is 0.6-0.8:0.2-0.5:0.1-0.6:0.02-0.1. By controlling the mass ratio of lithium iron phosphate, PTC material, conductive agent, and binder, the present invention minimizes cell capacity loss and achieves a high needle puncture safety pass rate.
[0009] The above-mentioned laminated lithium-ion battery using a safety primer slurry to improve safety performance is characterized in that the lithium iron phosphate is prepared by a sol-gel method and is obtained after hydrolysis, gelation, drying and dehydration, and roasting and grinding. The specific surface area of the lithium iron phosphate is 12m 2 / g~15m 2 / g, and a particle size distribution D50 of 0.9μm to 1.1μm. The present invention adopts a sol-gel method to prepare lithium iron phosphate, while limiting the specific surface area and particle size of lithium iron phosphate, mainly to improve the safety performance of the material. A moderate specific surface area has a low surface energy, which avoids catalytic electrolyte decomposition.
[0010] The aforementioned laminated lithium-ion battery employing a safety primer slurry to enhance safety is characterized in that the PTC material comprises one or more of strontium titanate, barium titanate, silicon oxide, aluminum oxide, and barium sulfate. By controlling the specific composition of the PTC material, the present invention achieves a PTC effect even in high-temperature environments, thereby increasing the internal resistance of the battery cell and the resistance to electron conduction.
[0011] The aforementioned laminated lithium-ion battery employing a safety primer slurry to enhance safety is characterized in that the conductive agent comprises one or more of acetylene black, carbon graphite fibers, and carbon nanotubes. The present invention controls the composition of the conductive agent and selects a specific conductive agent based on the desired application. Acetylene black transmits electrons through point-to-point contact within the material, carbon graphite fibers primarily conduct electricity through surface-to-point contact within the material, and nanotubes primarily transmit electrons through line-to-point contact within the material. The combined use of these conductive agents allows for multiple conduction modes within the material, thereby improving the material's electrical conductivity.
[0012] The above-mentioned laminated lithium-ion battery using a safety primer slurry to improve safety performance is characterized in that the binder includes one or more of polyvinylidene fluoride, polymethyl methacrylate, and polyacrylic acid. By controlling the composition of the binder, the present invention has high tensile strength, good bonding performance, and excellent chemical and environmental stability. For example, the C-F bond in polyvinylidene fluoride has a short bond length and high bond energy, and has excellent oxidation resistance and chemical corrosion resistance. It also has excellent bonding performance, can effectively bond the various components in the safety primer slurry, and reduce the contact impedance between the various components.
[0013] The aforementioned laminated lithium-ion battery using a safety primer slurry to improve safety performance is characterized in that the thickness of the safety coating is 5 μm to 10 μm. By controlling the thickness of the safety coating, the present invention avoids the problem of excessively thick coating causing excessive internal resistance of the battery, which is detrimental to the rate and cycle performance of the battery cell, and the problem of excessively thin coating causing no increase in the internal resistance of the battery cell.
[0014] The above-mentioned laminated lithium-ion battery that uses a safety primer slurry to improve safety performance is characterized in that the positive electrode current collector is made of aluminum foil, and the thickness of the positive electrode current collector is 9μm to 12μm. The present invention uses a positive electrode current collector made of aluminum foil and controls the thickness, thereby controlling the thermal conductivity inside the battery and improving the internal thermal conductivity coefficient during the battery cell puncture process.
[0015] The aforementioned laminated lithium-ion battery employing a safety primer slurry to enhance safety performance is characterized in that the positive electrode slurry utilizes lithium cobalt oxide or a nickel-cobalt-manganese ternary material with a cutoff voltage of no greater than 4.4V. By controlling the composition and cutoff voltage of the positive electrode slurry, the present invention achieves a low needle puncture rate, highlighting the significant role of the safety coating material. Furthermore, since a higher cutoff voltage leads to less stable material and a lower needle puncture rate, the current material cutoff voltage is limited to no more than 4.4V.
[0016] Compared with the prior art, the present invention has the following advantages:
[0017] 1. The present invention introduces a safety primer material into a laminated lithium-ion battery, synthesizes the safety primer material through formula optimization, and then coats the surface of the positive current collector to obtain a positive current collector with a safety coating. On this basis, coating is performed to obtain a positive electrode sheet with a safety coating. It can not only provide active lithium ions for lithium insertion and extraction, thereby improving the battery capacity, but also as the temperature rises to the critical point, the internal resistance instantly increases, which can effectively prevent the insertion and extraction of active lithium, reduce the electrochemical reaction rate, improve the safety performance of the battery under extreme conditions, and avoid the occurrence of safety accidents.
[0018] 2. The present invention mixes lithium iron phosphate, PTC material, conductive agent and binder in a certain mass ratio, and uses N-methylpyrrolidone as a dispersion medium to prepare a safety primer slurry, thereby preparing a safety coating. The safety coating is not only sensitive to temperature, but also has an internal resistance that increases instantaneously when the temperature is greater than or equal to 130°C, which can instantly reduce the short-circuit current of the battery and avoid the violent electrochemical reaction that releases a large amount of heat. At the same time, the lithium iron phosphate material with better safety effectively reduces the capacity loss caused by the primer, and the battery capacity loss is small. The obtained laminated lithium-ion battery has higher safety performance during the acupuncture process.
[0019] 3. The safety coating of the present invention contains PCT material, which is inherently non-flammable, can reduce the possibility of battery fire and explosion, improve the safety performance of lithium cobalt oxide or ternary system batteries, and has the characteristics of simple operation, low cost, and easy mass production.
[0020] 4 Compared with the prior art, the present invention has a simpler preparation method and does not require complex changes in the battery structure, so there is no need to modify the existing equipment. It has the advantages of low preparation cost and strong adaptability to existing processes.
[0021] The technical solution of the present invention is further described in detail below through the accompanying drawings and embodiments. BRIEF DESCRIPTION OF THE DRAWINGS
[0022] Figure 1 This is a comparison chart of the capacity test results of the laminated lithium-ion battery with a safety coating prepared in Example 1 of the present invention and the laminated lithium-ion battery without a safety coating prepared in Comparative Example 1.
[0023] Figure 2 This is a graph showing the results of a needle penetration test on a laminated lithium-ion battery with a safety coating prepared in Example 1 of the present invention.
[0024] Figure 3 This is a graph showing the results of a needle penetration test on a laminated lithium-ion battery without a safety coating prepared in Comparative Example 1 of the present invention.
[0025] Figure 4The data of temperature rise and voltage during the acupuncture process of the laminated lithium-ion battery with a safety coating prepared in Example 1 of the present invention.
[0026] Figure 5 The data of temperature rise and voltage during the acupuncture process of the laminated lithium-ion battery without a safety coating prepared in Comparative Example 1 of the present invention are shown. DETAILED DESCRIPTION
[0027] Example 1
[0028] This embodiment includes the following steps:
[0029] Step 1: Using the sol-gel method, through hydrolysis, gelation, drying and dehydration, and roasting and grinding, a specific surface area of 12m 2 / g, lithium iron phosphate with a particle size distribution D50 of 1.1 μm;
[0030] Step 2: The lithium iron phosphate, strontium titanate, carbon nanotubes and polyvinylidene fluoride obtained in step 1 are mixed in a mass ratio of 0.7:0.4:0.4:0.05, and then N-methylpyrrolidone is used as a dispersion medium, and the mixture is stirred at high speed to obtain a safety primer slurry;
[0031] Step 3: Apply the safety coating slurry obtained in step 2 to the outer surface of a positive electrode current collector made of aluminum foil with a thickness of 10 μm, and then dry it to obtain a positive electrode current collector with a safety coating with a thickness of 10 μm;
[0032] Step 4: The outer side of the positive electrode current collector with the safety coating obtained in step 3 is further coated with a lithium cobalt oxide positive electrode slurry with a thickness of 98 μm and a cut-off upper limit voltage of no more than 4.4 V to obtain a positive electrode sheet with a safety coating;
[0033] Step 5: The positive electrode sheet with the safety coating obtained in step 4 is stacked with the corresponding separator and negative electrode sheet, and then the stacked sheets are packaged in a shell, baked, injected with electrolyte, aged, and formed to obtain a stacked lithium-ion battery with a safety coating.
[0034] In this embodiment, the PTC material may also be one or more of strontium titanate, barium titanate, silicon oxide, aluminum oxide and barium sulfate, the conductive agent may also be one or more of acetylene black, carbon graphite fiber and carbon nanotubes, and the binder may also be one or more of polyvinylidene fluoride, polymethyl methacrylate and polyacrylic acid.
[0035] Comparative Example 1
[0036] This comparative example comprises the following steps:
[0037] Step 1: Coat the outer side of the positive electrode current collector with a lithium cobalt oxide positive electrode slurry having a cut-off upper limit voltage of no more than 4.4V and a thickness of 98 μm to obtain a positive electrode sheet without a safety coating;
[0038] Step 2: The positive electrode sheet without the safety coating obtained in step 1 is stacked with the corresponding separator and negative electrode sheet, and then the stacked sheets are packaged in a shell, baked, injected with electrolyte, aged, and formed to obtain a stacked lithium-ion battery without the safety coating.
[0039] The capacity of the laminated lithium-ion battery with a safety coating prepared in Example 1 and the laminated lithium-ion battery without a safety coating prepared in Comparative Example 1 were tested. The results are shown in Table 1. Figure 1 ,from Figure 1 It can be seen that the battery capacity of the laminated lithium-ion battery with a safety coating prepared in Example 1 and the laminated lithium-ion battery without a safety coating prepared in Comparative Example 1 is not much different, indicating that the lithium iron phosphate in the safety coating can effectively provide active lithium and avoid capacity loss caused by the primer.
[0040] The laminated lithium ion battery with a safety coating prepared in Example 1 and the laminated lithium ion battery without a safety coating prepared in Comparative Example 1 were subjected to needle puncture tests. The results are shown in Table 1. Figures 2 to 5 ,from Figure 2 It can be seen that the needle puncture pass rate of the laminated lithium ion battery with a safety coating prepared in Example 1 is 100%. Figure 3 It can be seen that after the laminated lithium-ion battery without a safety coating prepared in Comparative Example 1 was punctured, the battery cell instantly caught fire and burned. Figure 4 It can be seen from the data that the open circuit voltage of the laminated lithium ion battery with a safety coating prepared in Example 1 has a tendency to drop suddenly in the early stage of the needling process, but as the needling process proceeds, the open circuit voltage gradually recovers and tends to be stable. This data preliminarily shows that in the early stage of the battery needling process, the heat released after the positive and negative electrodes short-circuit occurs, causing the internal resistance of the safety coating to increase instantly, thereby preventing the further occurrence of the short circuit, reducing the intensity of the electrochemical reaction inside the battery cell, and the voltage gradually remains stable. At the same time, combined with the temperature rise data during the needling process of the battery cell, it is further shown that the lithium ion battery coated with the safety primer material has excellent safety performance, can effectively prevent the battery from catching fire during the needling process, and effectively improve the safety performance of the battery. Figure 5 It can be seen that the surface of the positive electrode sheet of the laminated lithium ion without safety coating prepared in Comparative Example 1 is not coated with a safety coating. During the puncture process, the temperature of the battery cell rises sharply and the voltage drops instantaneously, indicating that an obvious short circuit point occurs inside the battery cell, causing the battery cell to catch fire instantly.
[0041] By comparing Example 1 with Comparative Example 1, it can be seen that Example 1 greatly improves the safety performance of the laminated lithium-ion battery by providing the safety coating.
[0042] Example 2
[0043] This embodiment includes the following steps:
[0044] Step 1: Using the sol-gel method, after hydrolysis, gelation, drying and dehydration, roasting and grinding, a specific surface area of 13m 2 / g, lithium iron phosphate with a particle size distribution D50 of 0.9 μm;
[0045] Step 2: The lithium iron phosphate, strontium titanate, carbon nanotubes and polyvinylidene fluoride obtained in step 1 are mixed in a mass ratio of 0.6:0.2:0.6:0.02, and then N-methylpyrrolidone is used as a dispersion medium, and the mixture is stirred at high speed to obtain a safety primer slurry;
[0046] Step 3: Apply the safety coating slurry obtained in step 2 to the outer surface of a positive electrode current collector made of aluminum foil with a thickness of 9 μm, and then dry it to obtain a positive electrode current collector with a safety coating with a thickness of 5 μm;
[0047] Step 4: The outer side of the positive electrode current collector with the safety coating obtained in step 3 is further coated with a lithium cobalt oxide positive electrode slurry with a thickness of 98 μm and a cut-off upper limit voltage of no more than 4.4 V to obtain a positive electrode sheet with a safety coating;
[0048] Step 5: The positive electrode sheet with the safety coating obtained in step 4 is stacked with the corresponding separator and negative electrode sheet, and then the stacked sheets are packaged in a shell, baked, injected with electrolyte, aged, and formed to obtain a stacked lithium-ion battery with a safety coating.
[0049] In this embodiment, the PTC material may also be one or more of strontium titanate, barium titanate, silicon oxide, aluminum oxide and barium sulfate, the conductive agent may also be one or more of acetylene black, carbon graphite fiber and carbon nanotubes, and the binder may also be one or more of polyvinylidene fluoride, polymethyl methacrylate and polyacrylic acid.
[0050] Example 3
[0051] This embodiment includes the following steps:
[0052] Step 1: Using the sol-gel method, through hydrolysis, gelation, drying and dehydration, and roasting and grinding, a specific surface area of 15m 2 / g, lithium iron phosphate with a particle size distribution D50 of 1.0 μm;
[0053] Step 2: The lithium iron phosphate, strontium titanate, carbon nanotubes and polyvinylidene fluoride obtained in step 1 are mixed in a mass ratio of 0.8:0.5:0.1:0.1, and then N-methylpyrrolidone is used as a dispersion medium, and the mixture is stirred at a high speed to obtain a safety primer slurry;
[0054] Step 3: Apply the safety coating slurry obtained in step 2 to the outer surface of a positive electrode current collector made of aluminum foil with a thickness of 12 μm, and then dry it to obtain a positive electrode current collector with a safety coating with a thickness of 8 μm;
[0055] Step 4: The outer side of the positive electrode current collector with the safety coating obtained in step 3 is further coated with a nickel-cobalt-manganese ternary material positive electrode slurry with a thickness of 98 μm and a cut-off upper limit voltage of no more than 4.4 V to obtain a positive electrode sheet with a safety coating;
[0056] Step 5: The positive electrode sheet with the safety coating obtained in step 4 is stacked with the corresponding separator and negative electrode sheet, and then the stacked sheets are packaged in a shell, baked, injected with electrolyte, aged, and formed to obtain a stacked lithium-ion battery with a safety coating.
[0057] In this embodiment, the PTC material may also be one or more of strontium titanate, barium titanate, silicon oxide, aluminum oxide and barium sulfate, the conductive agent may also be one or more of acetylene black, carbon graphite fiber and carbon nanotubes, and the binder may also be one or more of polyvinylidene fluoride, polymethyl methacrylate and polyacrylic acid.
[0058] The above description is only a preferred embodiment of the present invention and does not limit the present invention in any way. Any simple modification, change and equivalent variation made to the above embodiment based on the technical essence of the present invention shall still fall within the scope of protection of the technical solution of the present invention.
Claims
1. A laminated lithium-ion battery using a safety primer slurry to improve safety performance, characterized in that: The laminated lithium-ion battery includes a battery shell and a battery cell inside the battery shell. The battery cell includes a laminated positive electrode sheet, a separator, a negative electrode sheet, and an electrolyte. The positive electrode sheet includes a positive electrode collector. The outer surface of the positive electrode collector is provided with a safety coating. The outer side of the safety coating is coated with a positive electrode slurry. The safety coating is formed by spraying a safety primer slurry onto the surface of the positive electrode collector and then drying it. The safety primer slurry is prepared by mixing lithium iron phosphate, PTC material, a conductive agent, and a binder, using N-methylpyrrolidone as a dispersion medium, and undergoing high-speed stirring.
2. The laminated lithium-ion battery with improved safety performance using a safety primer slurry according to claim 1, characterized in that: The mass ratio of lithium iron phosphate, PTC material, conductive agent and binder in the safety primer slurry is 0.6-0.8:0.2-0.5:0.1-0.6:0.02-0.
1.
3. The laminated lithium-ion battery with improved safety performance using a safety primer slurry according to claim 1, characterized in that: The lithium iron phosphate is prepared by the sol-gel method and is obtained after hydrolysis, gelation, drying and dehydration, and roasting and grinding. The specific surface area of the lithium iron phosphate is 12m 2 / g~15m 2 / g, and the particle size distribution D50 is 0.9μm to 1.1μm.
4. The laminated lithium-ion battery with improved safety performance using a safety primer slurry according to claim 1, characterized in that: The PTC material includes one or more of strontium titanate, barium titanate, silicon oxide, aluminum oxide and barium sulfate.
5. The laminated lithium-ion battery with improved safety performance using a safety primer slurry according to claim 1, characterized in that: The conductive agent includes one or more of acetylene black, carbon graphite fiber and carbon nanotube.
6. The laminated lithium-ion battery with improved safety performance using a safety primer slurry according to claim 1, characterized in that: The binder includes one or more of polyvinylidene fluoride, polymethyl methacrylate, and polyacrylic acid.
7. The laminated lithium-ion battery with improved safety performance using a safety primer slurry according to claim 1, characterized in that: The thickness of the safety coating is 5 μm to 10 μm.
8. The laminated lithium-ion battery with improved safety performance using a safety primer slurry according to claim 1, characterized in that: The positive electrode current collector is made of aluminum foil, and the thickness of the positive electrode current collector is 9 μm to 12 μm.
9. The laminated lithium-ion battery with improved safety performance using a safety primer slurry according to claim 1, characterized in that: The positive electrode slurry adopts lithium cobalt oxide or nickel-cobalt-manganese ternary material with a cut-off upper limit voltage not greater than 4.4V.